Evolution of the sex determination pathway in the Mediterranean flour moth, Ephestia kuehniella - Visser, Sander (Jihočeská univerzita, 2021)
The sex determination pathway in insects is a fast evolving gene cascade. In particular, the genes at the top of this cascade differ even between closely related species. This study explores the sex determination pathway of the Mediterranean flour moth, Ephestia kuehniella, which is widely used as a food source for the mass rearing of biological control agents. Therefore, an ortholog of the Masculinizer gene was identified and its role in sex determination was assessed by applying RNA interference (RNAi). In addition, a putative feminizing gene was identified on the W chromosome of E. kuehniella and a closely related species, and their genetic structure was determined by qPCR, Southern hybridization, and fluorescence in situ hybridization. The data contribute to our understanding of the sex-determining system in E. kuehniella and the evolution of the sex determination pathway in Lepidoptera.
Evolution of the sex determination pathway in the Mediterranean flour moth, Ephestia kuehniella
Keywords: Ephestia kuehniella; sex determination; Masculinizer; Feminizer; Plodia interpunctella; Lepidoptera; gene duplication; Ephestia kuehniella; sex determination; Masculinizer; Feminizer; Plodia interpunctella; Lepidoptera; gene duplication